2019
DOI: 10.1088/1742-6596/1402/7/077050
|View full text |Cite
|
Sign up to set email alerts
|

Stress meter: Android-based assessment application for academic stress level of students

Abstract: Academic stress is one of the negative emotional levels that can affect students’ physical, psychological, and academic health. Thus, there needs to be an assessment media that utilizes technological developments but can still evaluate academic stress levels effectively and efficiently. The purpose of this study was to develop an android-based assessment media (Stress Meter) that is able to measure students’ academic stress levels. This study used research and development methods. Data obtained were analyzed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The use of an Android-based stress assessment application has been implemented by [32] to measure stress levels in students. Several previous studies have shown that the use of stress assessment instruments Android-based can measure levels of depression, anxiety and stress and is good for implementation [19] [33]. Android is a mobile application that is quite popular because of the speed factor, namely the efficiency of the application in providing data according to the user's wishes [34].…”
Section: Table 9 Analysis Of Trials With System Usability Scale (Sus)mentioning
confidence: 99%
“…The use of an Android-based stress assessment application has been implemented by [32] to measure stress levels in students. Several previous studies have shown that the use of stress assessment instruments Android-based can measure levels of depression, anxiety and stress and is good for implementation [19] [33]. Android is a mobile application that is quite popular because of the speed factor, namely the efficiency of the application in providing data according to the user's wishes [34].…”
Section: Table 9 Analysis Of Trials With System Usability Scale (Sus)mentioning
confidence: 99%